The interaction between gold price and FTSE KLCI price in Malaysia - Sook, Ching Kok; Qaiser Munir (Faculty of Business, Economics and Accountancy, 2021)
This paper intends to study the interaction between FTSE KLCI price and gold price in Malaysia. It is found that there is cointegration relationship between log FTSE KLCI return and log gold return. Besides that, log gold return Granger cause log FTSE KLCI return which suggest the inclusion of both investments in a same portfolio. This is proposed so that to have the benefit of diversification to reduce investment risk. If a rise in gold return leads to a fall in FTSE KLCI return, then the two investments can be the substitute to each other. If a rise in gold return leads to a rise in FTSE KLCI return, the two investments can be complements.